Control en las actividades económicas tributarias de las organizaciones no financieras de la economía popular y solidaria en Ecuador - Cuesta Mendieta, Johanna Patricia (2020)
Consolidate a tributary culture that allows a level of awareness of the rights and duties that derive for the passive subjects of the tax relationship is fundamental for the State's economy. The research consisted in the analysis of control in the tax economic activities of non-financial Organizations of the Popular and Solidarity Economy in Ecuador, regarding the fulfillment of the duties and formal rights referred to national taxes to manage with a conscience and ethics their obligations to the state once they become an organization. The study was carried out under a non-experimental design, on the basis of theories used by different authors and through the document review, of which took some references as background and theories that gave support to this research. As a technique and instruments collection is conducted a survey of closed type to a population of the present investigation was obtained from the Superintendence of Popular and Solidarity Economy, zonal 5 the non-financial sector because of the 12.779 registered organizations at country level with cut to 31 December 2017, a total of 3.990 of them comprise five provinces: El Oro, Galápagos, Guayas, Los Ríos y Santa Elena.